A year in the public life of superbugs: News media on antimicrobial resistance and implications for health communications. (July 2020) - Davis, Mark; Lyall, Benjamin; Whittaker, Andrea; Lindgren, Mia; Djerf-Pierre, Monika; Flowers, Paul
Abstract: News media can be an important source of information about emerging health threats. They are also significant sites for the production of narrative on threats to life that help to condition and reflect the responses of governments and publics. Antimicrobial resistance (AMR) is one such health threat with particular significance because it represents the failure to manage the risks to antibiotics and other antimicrobials, health technologies that have provided the basis for modern medicine. Knowledge of how news media address this situation is an important element for an effective public health response to AMR and helps to extend the social analysis of health and media. Based on an analysis of television, printed and digital news for 2017 in Australia, this paper examines the patterns and meanings of AMR news. It shows that AMR is a fragmented story mainly framed by scientific discovery. These stories reassure audiences that science is seeking out the means of arresting AMR and, therefore, also constructs lay publics as passive witnesses to the AMR story. This pattern of AMR story-telling furthers the social standing of science and scientists, but it also neglects deliberation on collective action, important lacunae in the social response to AMR. Highlights: Digital news sources fragment narratives on antimicrobial resistance (AMR). TV, printed and digital news mainly draw on discovery narratives to explain AMR. Discovery narratives further scientific authority but foreclose audience agency. Alternative narratives are needed to promote public engagement with AMR.